1992
DOI: 10.3109/07853899209149959
|View full text |Cite
|
Sign up to set email alerts
|

Binge Eating in the Obese

Abstract: This review will first describe problems in the definition of the term binge eating, especially in the absence of purging (vomiting, laxative abuse). We highlight current approaches in the classification of obesity, and then provide an overview of the available literature on differences between obese binge eaters and obese non-binge eaters. Many studies indicate that binge eating is common among the female obese, with a frequency ranging from 23 to 46% among those seeking treatment for weight reduction. Despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 37 publications
5
17
0
1
Order By: Relevance
“…The most likely explanation for this difference is that we did not restrict our analysis to young obese women as done by most studies (7,31,32) . Including males, elders and normal-weight subjects, as we deliberately did here, is expected to decrease the overall prevalence of BE.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation for this difference is that we did not restrict our analysis to young obese women as done by most studies (7,31,32) . Including males, elders and normal-weight subjects, as we deliberately did here, is expected to decrease the overall prevalence of BE.…”
Section: Discussionmentioning
confidence: 99%
“…of the Diagnostic and Statistical Manual of Mental Disorders (DSM-IV; American Psychiatric Association [APA], 1994) has spawned a considerable body of research (de Zwaan & Mitchell, 1992). Using DSM-IV criteria, the defining characteristics of BED are (1) consumption of an objectively large amount of food in a discrete time period, (2) a lack of control during the eating episode, and (3) a lack of compensatory behavior following a binge (APA, 1994).…”
Section: Bedmentioning
confidence: 99%
“…1,2 One group of behavioural traits that may generate imbalance in the energy regulation by increasing energy intake, and hence possibly relate to obesity and weight gain, are abnormal eating patterns such as restrained eating, binge eating and night eating. [3][4][5][6][7][8][9][10] The night-eating syndrome was described in 1955 as a condition characterised by morning anorexia (minimal or no calorie intake at breakfast), evening hyperphagia (at least 50% of daily calorie intake after the evening meal) and insomnia, and it has later been broadened to include night time awakenings with food intake. [11][12][13][14] Several studies have used this definition and found frequencies of the night-eating syndrome ranging from 8 to 27% among obese patients.…”
Section: Introductionmentioning
confidence: 99%